If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6p(p + -8) = 0 Reorder the terms: 6p(-8 + p) = 0 (-8 * 6p + p * 6p) = 0 (-48p + 6p2) = 0 Solving -48p + 6p2 = 0 Solving for variable 'p'. Factor out the Greatest Common Factor (GCF), '6p'. 6p(-8 + p) = 0 Ignore the factor 6.Subproblem 1
Set the factor 'p' equal to zero and attempt to solve: Simplifying p = 0 Solving p = 0 Move all terms containing p to the left, all other terms to the right. Simplifying p = 0Subproblem 2
Set the factor '(-8 + p)' equal to zero and attempt to solve: Simplifying -8 + p = 0 Solving -8 + p = 0 Move all terms containing p to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + p = 0 + 8 Combine like terms: -8 + 8 = 0 0 + p = 0 + 8 p = 0 + 8 Combine like terms: 0 + 8 = 8 p = 8 Simplifying p = 8Solution
p = {0, 8}
| x=28+-4y | | w-17+4w-16= | | -1-(-36)= | | x=3y^2 | | 29.6-t=-3.9 | | x+4y=29 | | 6x+5x=174 | | -1+5-(-30)-15= | | 4b^2-2b=0 | | -21-(-22)+(-1)-11= | | -5-(-6)+(-2)= | | 7x-2x-11=x+5x | | 4.7-7.2y=-62.3 | | 6-(-14)+(-21)= | | -13+(-2)-11= | | (X+2)(x+2)=x^2+4 | | -4-11-(-15)= | | x^2-8x+5=x^2-8x+16-11 | | 5x-12-3x=4 | | 11-5-17= | | 2-2-9= | | 4(y-3)+2(y+4)=20 | | 11+3t=5t-15 | | 14x=4x+80 | | -5d+10=-25 | | 17w+6w= | | 2x^2-3=-35 | | 2(x-1)-4(3-2x)=1 | | 2x^2+5=103 | | -5(d-2)=-25 | | 2(5)= | | 2(2)= |